Variation of deoxynivalenol levels in corn and its products available in retail markets of Punjab, Pakistan and estimation of risk assessment - Iqbal, Shahzad Zafar; Abdull Razis, Ahmad Faizal; Usman, Sunusi; Ali, Nada Basheir; Asi, Muhammad Rafique (MDPI AG, 2021)
This study investigated the natural incidence of deoxynivalenol (DON) in corn and corn products from corn-producing districts of Punjab, Pakistan. The analysis was carried out using high performance liquid chromatography (HPLC) with UV detector and immunoaffinity cleanup columns. The detection limit (LOD) and limit of quantification were 25 and 50 µg/kg, respectively. A total of 1220 samples of corn and corn products were analyzed to detect DON, and 539 (44.2%) samples were observed to be contaminated with DON (n ≥ LOD). Furthermore, 92 (7.5%) samples of corn and corn products had DON levels that were higher than the proposed limits of the EU. The data are significantly different from a normal distribution of DON in samples of corn and corn products from different locations (p < 0.05) for Shapiro–Wilk and Kolmogorov–Smirnov values. However, a significant difference in DON levels was found between corn and corn-derived products (p ≤ 0.05). The lowest and highest exposures, and hazard quotient (HQ) values of 0.92 and 9.68 µg/kg bw/day, were documented in corn flour samples.